Phase I Clinical Trial Using [99mTc]Tc-1-thio-D-glucose for Diagnosis of Lymphoma Patients - Chernov V. I. Vladimir Ivanovich; Dudnikova E. A. Ekaterina Aleksandrovna; Zelchan (Zeltchan) R. V. Roman Vladimirovich; Medvedeva А. А. Anna Aleksandrovna; Rybina A. N. Anastasiya Nikolaevna; Bragina O. D. Olga Dmitrievna; Goldberg V. Victor; Muravleva A. Albina; Sorensen J. Jens; Tolmachev V. M. Vladimir Maksimilianovich (2022, 2022)
Similar to [18F]-FDG, [99mTc]Tc-1-thio-D-glucose ([99mTc]Tc-TG) also binds to GLUT receptors. The aim of this Phase I study was to evaluate the safety, biodistribution and dosimetry of [99mTc]Tc-TG. Twelve lymphoma patients were injected with 729 ± 102 MBq [99mTc]Tc-TG. Wholebody planar imaging was performed in 10 patients at 2, 4, 6 and 24 h after injection. In all 12 patients, SPECT/CT (at 2 h) and SPECT (at 4 and 6 h) imaging was performed. Vital signs and possible side effects were monitored during imaging and up to 7 days after injection. [99mTc]Tc-TG injections were well-tolerated and no side effects or alterations in blood and urine analyses data were observed. The highest absorbed dose was in the kidneys and urinary bladder wall, followed by the adrenals, prostate, bone marrow, lungs, myocardium, ovaries, uterus, liver and gall bladder wall. [99mTc]TcTG SPECT/CT revealed foci of high activity uptake in the lymph nodes of all nine patients with known nodal lesions. Extranodal lesions were detected in all nine cases. In one patient, a lesion in the humerus head, which was not detected by CT, was visualized using [99mTc]Tc-TG. Potentially, [99mTc]Tc-TG can be considered as an additional diagnostic method for imaging GLUT receptors in lymphoma patients.